Outcomes of patients undergoing surgery for thymic carcinoma: a single-center experience - Nabe, Yusuke; Ichiki, Yoshinobu; Fukuichi, Yukiko; Mori, Masataka; Honda, Yohei; Kanayama, Masatoshi; Taira, Akihiro; Shinohara, Shinji; Kuwata, Taiji; Takenaka, Masaru; Chikaishi, Yasuhiro; Oka, Soichi; et al. (Journal of Thoracic Disease; Vol 10, No 7 (July 31, 2018): Journal of Thoracic Disease, 2018)
Background: Thymic carcinoma is uncommon, presents locally at an advanced stage, and behaves aggressively. The optimum treatment for advanced thymic carcinoma is controversial. We retrospectively reviewed our institutional experience with patients with thymic carcinoma. Methods: We analyzed the clinical data of six patients who underwent total thymectomy for thymic carcinoma at our institution from 2006 to 2016. Variables analyzed included sex, age, histological classification, Masaoka staging, postoperative treatment, and recurrence. Results: The clinical characteristics of the six patients with thymic carcinoma (median age, 56 years; five men and one woman) were as follows: squamous cell carcinoma (n=5); sarcomatoid carcinoma (n=1); Masaoka stages II (n=1), III (n=2), IVa (n=1), and IVb (n=2). Four patients underwent combined pulmonary resection (66.7%) as a component of en bloc resection due to suspicion of pulmonary invasion. Four patients (66.7%) received postoperative therapy, and complete resection was achieved for four patients. There were no perioperative deaths. One patient experienced a recurrence. Conclusions: Complete resection for thymic cancer improved the prognosis of our patients, indicating that robust studies will be required to confirm our findings.